Serum immunoglobulin E and absolute eosinophil count as markers of severity in childhood asthma - Trivedi, Pinakin P.; Patel, Ami H. (International Journal of Contemporary Pediatrics, 2020)
Background: Asthma is a chronic inflammatory condition of the airways resulting in increased airway reactivity to a variety of stimuli like allergens, irritants, viruses and exercise. There is a strong association between the exposure of allergens and development of asthmatic symptoms. A hypersensitivity reaction initiated by immunologic mechanisms mediated by Immunoglobulin E (IgE) antibodies occurs in allergic asthma. IgE and eosinophils play an important role in the inflammatory process resulting in bronchial hyperresponsiveness. The aim of this study was to evaluate serum total IgE levels and Absolute Eosinophil Count (AEC) as markers of disease activity and study their association with the severity of bronchial asthma in children. Methods: A prospective study was conducted in the paediatric department of a tertiary care hospital in Ahmedabad, Gujarat, India from July 2017 to December 2018. Children between 4-14 years of age diagnosed as having bronchial asthma were included in the study. Serum total IgE levels and absolute eosinophil count were done in all the study participants and their correlation with the severity of asthma was assessed. Results: Of the total 109 patients of asthma, 44(40.4%) had intermittent asthma, 30(27.5%) mild persistent, 25(22.9%) moderate persistent and 10(9.2%) severe persistent asthma. Serum total IgE levels were raised above the normal limits for age in 94(86.2%) patients and increased AEC was found in 61(56 %) patients. Both serum total IgE levels and AEC increased significantly (p<0.0001) with increasing severity of asthma. Conclusions: Serum total IgE levels and AEC can be used to predict the severity of asthma in children.